A fast-responsive fluorescent probe for sensitive detection of graphene oxide based on MoS2 quantum dots. Issue 13 (5th June 2018) - Cao, Haiyan; Huang, Yu; Xie, Yuanyang; Shi, Wenbing; Fu, Cuicui; He, Wei
Abstract : N-MoS2 QDs showed excellent stability, and were used to build a simple fluorescence probe for the determination of GO. Abstract : Facile preparation of water soluble and fluorescent N-doped MoS2 quantum dots (N-MoS2 QDs) is described herein. N was introduced to reduce defects in the MoS2 surface. The obtained N-MoS2 QDs exhibited excellent fluorescence characteristics with good photostability and excellent stability even in 3 M NaCl solution and when stored in a refrigerator for one year. Additionally, the fluorescent N-MoS2 QDs were developed as a simple and practical nanosensor for the detection of GO through hydrophobic π–π interactions between N-MoS2 QDs and GO, where the excited state electron and energy transfer may occur from N-MoS2 QDs to GO along with fluorescence quenching of N-MoS2 QDs. These results reveal that the limit of detection (LOD) was as low as 4 ng mL −1, which was able to satisfy the needs of the determination of GO in environmental water samples. Importantly, the N-MoS2 QDs nanosensor exhibits excellent detection selectivity against other ions or molecules in the environment. In this study, the proposed sensor was successfully used for the determination of GO content in environmental water samples.